Price and Quantity Patterns When the Consumers' Income is Uncertain - Corrado Benassi; Roberto Cellini; Alessandra Chirco (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
The paper shows that the co-movements of optimal price and output in a monopolistic market can be a case of spurious correlation, price and quantity variations being affect by the degree of uncertainty in the consumers' incomes. The pattern of price and quantity changes depends on the shape of the distribution function of the stochastic variable "income of the consumers", as well as the size of the firm's costs.
Keywords: 330